Preparation of medicinal plant rhizome Bay la mot hoa (Paris polyphylla Smith) under various drying conditions - Thanh Giang Tran; Van Hoa Nguyen; Thi Van Nguyen; Van Tang Nguyen (Cogent Food & Agriculture)
Paris polyphylla Smith has been used in many traditional medicinal treatments. However, there has been no previous research on the application of advanced drying technologies to prepare dried P. polyphylla Sm. rhizomes. This study aimed at identifying the influence of various drying conditions on the physicochemical, phytochemical, and antioxidant properties of P. polyphylla Sm. rhizomes. The findings clearly showed that all drying conditions could reduce the residual moisture and water activity to safe storage values. Microwave drying had the shortest drying time and energy consumption (0.17–0.73 h and 0.12–0.21 kWh), but this technique did not obtain high bioactive compounds and antioxidant activities. Freeze drying was the opposite of microwave drying, which possessed the greatest phytoconstituents (total saponin content 42.29 mg escin equivalents/g dry weight (DW), total phenolic content 0.58 mg gallic acid equivalents/g DW and total alkaloid content 0.25 mg atropine equivalents/g DW) and antioxidant capacity (ABTS radical scavenging capacity 2.66 mg trolox equivalents (TE)/g DW, DPPH radical scavenging capacity 2.01 mg TE/g DW and ferric reducing antioxidant power 1.49 mg TE/g DW), however this method consumed the most drying time and energy (48 h and 105.6 kWh). Therefore, among tested drying conditions, hot-air drying at 60 °C is recommended for preparing P. polyphylla Sm. rhizomes.